The preventive role of medical ozone therapy on remote organ injury induced by hepatic ischemia reperfusion (Annals of Medical Research, 2021)
Aim: This study explores the effects of ozone therapy on the prevention of remote organ injury in rats with induced hepatic ischemia reperfusion injury.Materials and Methods: Twenty-one male Sprague Dawley rats were sorted randomly into three groups: (a) A control group in which the rats’ abdomens were operated on by laparotomy, and their livers then viewed and closed with a suture; (b) Rats with induced hepatic ischemia-reperfusion injuries; and (c) Rats induced with the same injuries that were administered ozone therapy before reperfusion. The rats’ hepatic arteries, portal veins, and bile ducts were clamped, and ischemia was induced for 45 min. Reperfusion was provided for 90 min in the second and third groups. The third group was administered 0.5 mg/kg ozone intraperitoneally before reperfusion. Liver, lung, and kidney tissues were taken for biochemical and histopathological examinations.Results: In the second group, malondialdehyde levels in the lung and kidney tissues were higher than in the control group, while catalase and superoxide dismutase enzyme levels were lower. The third group had lower malondialdehyde levels and higher catalase and superoxide dismutase enzyme levels than the group that did not receive the therapy. In histopathological evaluations, the damage to both kidney and lung tissues in the third group was higher than in the control group; however, this damage was significantly lower than in the second group.Conclusions: The findings indicated that the administration of ozone therapy attenuated lung and kidney injuries caused by hepatic ischemia, since partial protection was demonstrated in many instances.
Keywords: Hepatic ischemia/reperfusion; kidney; lung; ozone; emote organ injury